Identification of the Prognostic Signature Associated With Tumor Immune Microenvironment of Uterine Corpus Endometrial Carcinoma Based on Ferroptosis-Related Genes - Liu, Jinhui; Wang, Yichun; Meng, Huangyang; Yin, Yin; Zhu, Hongjun; Ni, Tingting (Frontiers in Cell and Developmental Biology, 2021)
Background: Uterine corpus endometrial carcinoma (UCEC) is the sixth most common cancer worldwide. Ferroptosis plays an important role in malignant tumors. However, the study of ferroptosis in the endometrial carcinoma remains blank. Methods: Firstly, we constructed a ferroptosis-related signature based on the expression profiles from the Cancer Genome Atlas (TCGA) database. Then, patients were divided into the high-risk and low-risk groups based on this signature. The signature was evaluated by Kaplan-Meier analysis and receiver operating characteristic (ROC) analysis. We further investigated the relationship between this signature and immune microenvironment via CIBERSORT algorithm, ImmuCellAI, MAF, MSI sensor algorithm, GSEA and GDSC. Results: This signature could be an independent prognostic factor based on Multivariate Cox regression analysis. GSEA revealed that this signature was associated with immune-related phenotype. In addition, we indicated the different status of immune infiltration and response to the immune checkpoint between low-risk and high-risk groups. Patients in the low-risk group were more likely to present with a higher expression of immune checkpoint molecules and tumor mutation burden. Meanwhile, the low-risk patients showed sensitive responses to chemotherapy drugs. Conclusions: In summary, the six ferroptosis-related genes signature could be used in molecular subgrouping and accurately predict the prognosis of UCEC.